High-dose-rate brachytherapy monotherapy versus low-dose-rate brachytherapy with or without external beam radiotherapy for clinically localized prostate cancer. (March 2019) - Yamazaki, Hideya; Masui, Koji; Suzuki, Gen; Nakamura, Satoaki; Yamada, Kei; Okihara, Koji; Shiraishi, Takumi; Yoshida, Ken; Kotsuma, Tadayuki; Tanaka, Eiichi; Otani, Keisuke; Yoshioka, Yasuo; et al.
Highlights: A long-term data for HDR-BT monotherapy and LDR-BT with or without EBRT. LDR-BT showed equivalent PSA control and late toxicity ≥G2 GI and GU with HDR-BT. LDR-BT showed higher acute ≥G2 GU and late grade 1 GU toxicity. Acute GU toxicity predict late GU toxicity grade ≥G2. Additional EBRT with LDR-BT elevated GI toxicity to LDR-BT only. Abstract: Background: To compare the outcome of high-dose-rate interstitial brachytherapy (HDR-BT) monotherapy and low-dose-rate brachytherapy (LDR-BT) with or without external beam radiotherapy (EBRT) for localized prostate cancer. Methods and materials: We compared 352 patients treated with HDR-BT as monotherapy (median follow-up time 84 months, NCCN risk classification; low: intermediate: high = 28:145:179) and 486 patients with LDR-BT with or without EBRT (90 months, 194:254:38). HDR-BT treated advanced disease with more hormonal therapy than LDR-BT. LDR-BT excluded patients with T3b–T4 tumor and initial PSA >50 ng/ml. Inverse probability of treatment weighting (IPTW) involving propensity scores was used to reduce background selection bias. Results: The actuarial 5-year biochemical failure-free survival rates (bNED) were 92.9% and 95.6% ( p  = 0.25) in the HDR-BT and LDR-BT groups, respectively, and it was 100% and 97.3% ( p  = 0.99) in the low-risk, 95.6% and 94.3% ( p  = 0.19) in the intermediate, 89.6% and 94.9% ( p  = 0.26) in the high-risk groups, and 93.1% and 94.9% ( p  = 0.98) in selected high-risk group excluding T3b-4 and initial PSA ≥50. IPTW correction also indicated no difference in bNED between LDR-BT and HDR-BT groups. LDR-BT showed a higher incidence of genitourinary (GU) toxicity grade ≥2 than that of HDR-BT in the acute phase and grade 1 toxicity in late phase. Acute GU toxicity grade ≥1 predicted late GU toxicity grade ≥2. External beam radiotherapy plus LDR-BT elevated GI toxicity than LDR-BT only group. Accumulated incidence of late grade ≥2 GU and GU toxicity was equivalent between HDR-BT and LDR-BT. No grade 4 or 5 toxicities were detected in either modality. Conclusion: HDR-BT monotherapy showed an equivalent outcome to that of LDR-BT with or without EBRT for low-, intermediate- and selected high-risk patients. LDR-BT showed equivalent incidence of grade ≥2 late GI and GU toxicities and higher grade ≥2 acute GU toxicity as that of HDR-BT as a monotherapy.